Web-Based Acceptance and Commitment Therapy for Mental Health Problems in College Students: A Randomized Controlled Trial. (January 2017) - Levin, Michael E.; Haeger, Jack A.; Pierce, Benjamin G.; Twohig, Michael P.
There are significant challenges in addressing the mental health needs of college students. The current study tested an acceptance and commitment therapy (ACT), web-based self-help program to treat a broad range of psychological problems students struggle with. A sample of 79 college students was randomized to web-based ACT or a waitlist condition, with assessments at baseline and posttreatment. Results indicated adequate acceptability and program engagement for the ACT website. Relative to waitlist, participants receiving ACT improved on overall distress, general anxiety, social anxiety, depression, academic concerns, and positive mental health. There were no between-group effects on eating concerns, alcohol use, or hostility, or on some key ACT process of change measures. ACT participants improved more on mindful acceptance and obstruction to valued living, both of which mediated treatment outcomes. Results are discussed in the context of lessons learned with the website prototype, and areas for further research are presented.